Neurilemoma of the small intestine (Clinical case presentation) - I. D. Kalganov; A. P. Zhuchenko; I. V. Zarodnyuk; Ye. V. Markova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of clinical case presentation. To draw attention of specialists to rare neoplastic bowel diseases.Original points. Article presents the case of small intestinal neurilemoma in 69 years-old woman with incidental abdominal pain. Abdominal ultrasound investigation (US) was diagnostic (it demonstrated the volume lesion located at the loops of ileum with thickened vascularized walls) and helical computer tomography – CT (tumor with irregular outlines ileum, with the lobular heterogeneous structure was revealed, contrast agent accumulation was uneven). Ileectomy with formation of end-to-end anastomosis was carried out. The resected speciemen revealed signs of neurilemoma at histological study.Conclusion. It was possible to detect ileal tumor at abdominal US and CT. The diagnosis was verified at histological investigation.